Analisis Efektivitas Kemampuan Pulih Mandiri Micro Crack pada Self-Healing Concrete - Erfin Setiawan Setiawan; Yuni Sriwahyuni; Nia Kartika (Rekayasa Sipil, 2023)
The development of Self-Healing Concrete technology is a solution to overcome anomalies in concrete structures such as Micro Crack and is a preventive measure to prevent concrete damage. This study analyzes the effectiveness of Self-Healing Concrete which has the ability to recover independently when Micro Crack occurs in exposed concrete. The ability to recover independently of micro cracks was analyzed using Laboratory-based Visual Research Methods (VRM). The results showed that the application of Bacillus Subtilis bacteria as a Healing Agent on exposed concrete was effectively used to overcome Micro Crack below 0.607 mm with self-recovery of 93.98% at the age of the test sample of 56 days. And the value of the ability to recover independently was strengthened by SEM-EDX data which showed the morphological structure of the development of mycobacterial spores that filled the Micro Crack cavity was Calcium Carbonate (Ca-K) compound.